Strategy and Measures to Improve Breast Imaging Services at General Facility Hospital - Waheed, Khawaja Bilal; AlMaimouni, Alaa Ali; Hassan, Muhammad Zia Ul; Woodman, Alexander; Al-Jamea, Lamiaa H.; Albassam, Muneera Abdulhameed; Aloumi, Shayma Abdullah (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Breast cancer is one of the most commonly diagnosed cancers worldwide and is the most common cancer affecting women in Saudi Arabia. This research aims to highlight the strategy and measures needed to improve breast imaging services focusing on imaging justification, optimization, acquisition, and interpretation.The Find, Organize, Clarify, Understand, Select – Plan, Do, Check, Act (FOCUS-PDCA) methodology of quality improvement was adopted. In phase one, identification of deficiencies or problems was made by evaluating imaging requests, time management, workforce, and resource utilization between 2015 and 2017 (3 years). These were presented on a fishbone diagram. Optimization of services was made by appointing or training reliable breast imaging staff. The action plan and changes were subsequently implemented and their effects, in terms of improvement in justified imaging requests, increase in the number of screening studies, imaging acquisition, reporting by specialists, and adherence to a standard Breast Imaging-Reporting and Data System mammography reporting format, were evaluated from 2018 till the end of 2021.Total mammographic studies almost doubled in a year (from an average of 225 per annum in preintervention years to 443 exams postintervention), in which mammography screening studies increased three times in the postintervention period. Breast imaging referrals were streamlined primarily under primary care physicians and breast surgeons, with more than double referrals for the screening studies. Standard reporting was achieved in more than 90% of studies compared to 60% initially.Breast imaging services can be improved by promoting awareness and education to patients and primary physicians, streamlining imaging requests, properly utilizing time and resources, ensuring imaging acquisition, and interpretation by specialists.
Keywords: breast cancer; screening; imaging; quality assessment; fishbone diagram; FOCUS-PDCA